Recent Developments in the Catalytic Synthesis of 2-Substituted Benzoxazoles - He, Jian (Current Organic Chemistry, 2017)
Background: 2-Substituted benzoxazoles and their various derivatives are very important structures of functional materials, such as natural products, drug candidates, and biologically relevant compounds. Furthermore, they are multifunctional intermediates and synthons in a large number of functional group transformations and total syntheses. In last several decades, chemists have put forth tremendous effort and progress in the development of synthetic procedures for 2-substituted benzoxazoles preparation and applications in synthetic and medicinal field. Methodology: Catalytic synthesis of 2-substituted benzoxazoles can be classified into metal- and nonmetalcatalyzed processes simply. In the study of metal catalysis, the reactions are mainly performed using copper, palladium, iron, ruthenium, iridium; whereas, other metals such as zinc, cobalt, silver, gold based catalysts have also been explored to some extent. On the other hand, nonmetal-catalyzed 2-substituted benzoxazoles syntheses are generally restricted to Brønsted acid catalysts in the presence of or without other promoters. Objective: In this review, we are going to highlight the recent important research endeavors which are related to catalytic 2-substituted benzoxazoles synthesis.
Keywords: Benzoxazoles